Feasibility Analysis of Shallot Farming in Cimaung District, Bandung Regency (Case Study of Female Farming Customers of Bank BTPN Syariah) - Amalia Diandra; Sri Maryati; Pande Komang Suparyana (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2024)
This research aims to analyze the feasibility and determine the obstacles faced by Women Farming Customers of Bank BTPN Syariah in carrying out shallot farming in the Cimaung District. This research was conducted in Sukamaju Village which was determined using purposive sampling. Respondents were determined using